Promotional effect of CeO2 modified support on V2O5–WO3/TiO2 catalyst for elemental mercury oxidation in simulated coal-fired flue gas. (1st August 2015) - Zhao, Lingkui; Li, Caiting; Zhang, Jie; Zhang, Xunan; Zhan, Fuman; Ma, Jinfeng; Xie, Yin'e; Zeng, Guangming
Graphical abstract: Mechanism of CeO2 modified V2 O5 –WO3 /TiO2 catalysts for elemental mercury oxidation. Highlights: Nano-sized TiO2 –CeO2 mixed oxides is used as support material for Hg 0 oxidation. The Hg 0 oxidation activity of VWTi was promoted by support modification. There was synergistic effect between V2 O5 and CeO2 on Hg 0 oxidation. Hg 0 oxidation over V0.80 WTiCe0.25 follows a Mars–Maessen mechanism. Abstract: In order to enhance the catalytic activity for elemental mercury (Hg 0 ) oxidation without the aid of HCl, CeO2 was added into the support to modify V2 O5 –WO3 /TiO2 catalysts. The performance of V2 O5 –WO3 /TiO2 –CeO2 (VWTiCe) catalysts on Hg 0 oxidation as well as the catalytic mechanism was also studied. The catalysts were characterized by BET, XRD and XPS techniques. The results showed that the performance on Hg 0 oxidation was promoted by the introduction of CeO2 . NO and SO2 has a promoting effect on Hg 0 oxidation in the presence of O2 . Besides, the inhibitive effect of NH3 on Hg 0 oxidation was confirmed by NH3 consuming the surface oxygen of catalyst. The addition of CeO2 improved the ability to resist H2 O. Results also indicated that the Hg 0 oxidation efficiencies of V0.80 WTiCe0.25 catalysts were thought to be aided by synergistic effect between V2 O5 and CeO2 . Hg 0 oxidation over V0.80 WTiCe0.25 follows a Mars–Maessen mechanism where lattice oxygen of V2 O5 reacts with adjacently absorbed Hg 0 .